Crosslinked polyvinylpyrrolidone-polyethersulfone high-temperature proton exchange membrane, preparation method thereof, membrane electrode and fuel cell

By introducing surface tin bromide crosslinking agents into the polyvinylpyrrolidone-polyethersulfone composite film to form a crosslinking network and quaternary ammonium groups, the problem of difficulty in taking into account high mechanical strength and high proton conductivity of the composite film is solved, and the performance optimization of the film and the stability of the oxidation are improved.

CN119798906AActive Publication Date: 2025-04-11SHANGHAI INST OF SPACE POWER SOURCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411771731.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-11
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing polyvinylpyrrolidone-polyethersulfone composite membranes are difficult to take into account high proton conductivity and high mechanical strength. Ordinary crosslinking agents cause the polymer chain to be too tight to reduce proton conduction, and poor compatibility of inorganic fillers leads to reduced mechanical strength.

Method used

Using surface tin dioxide bromide as a crosslinking agent, a crosslinking network is formed by a nucleophilic substitution reaction with polyvinylpyrrolidone to form a crosslinking network to generate quaternary ammonium groups, enhancing mechanical strength and improving proton conductivity.

Benefits of technology

The optimal balance of mechanical strength and proton conductivity of the high-temperature proton exchange membrane is achieved, and the problems of excessive crosslinking and poor dispersion of inorganic fillers are avoided, and the film's anti-oxidation stability is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798906A_ABST
    Figure CN119798906A_ABST
Patent Text Reader

Abstract

The invention discloses a cross-linked polyvinylpyrrolidone-polyethersulfone high-temperature proton exchange membrane, a preparation method thereof, a membrane electrode and a fuel cell, the cross-linked polyvinylpyrrolidone-polyethersulfone high-temperature proton exchange membrane comprises a membrane main material and a cross-linking agent, the membrane main material comprises polyvinylpyrrolidone and polyethersulfone, the cross-linking agent is surface-brominated tin dioxide, and the addition mass ratio of the cross-linking agent is 1%-4% based on the membrane main material. The cross-linked polyvinylpyrrolidone-polyethersulfone high-temperature proton exchange membrane prepared by the invention has high proton conductivity and high mechanical strength, also has good oxidation resistance, and has wide application prospects in high-temperature proton exchange membrane fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a cross-linked polyvinyl pyrrolidone-polyether sulfone high-temperature proton exchange membrane, a preparation method thereof, a membrane electrode and a fuel cell. Background Art

[0002] With the widespread use of fossil fuels, global environmental pollution and energy shortages are becoming increasingly serious. Fuel cells, as an efficient and clean energy conversion technology, are gradually attracting widespread attention. Among them, proton exchange membrane fuel cells have the advantages of cleanliness and efficiency, fast startup and response speed, high power density, low noise, wide fuel adaptability, long life, and high reliability, and have received widespread attention and rapid development. According to the working temperature, proton exchange membrane fuel cells are divided into high-temperature proton exchange membrane fuel cells (working temperature is 120℃~200℃) and low-temperature proton exchange membrane fuel cells (working temperature <80℃). Compared with low-temperature proton exchange membrane fuel cells, high-temperature proton exchange membrane fuel cells (High Temperature Proton Exchange Membrane Fuel Cell, HT-PEMFC) have the advantages of high cell efficiency, simple water and heat management, and strong tolerance to CO catalysts. As the core component of high-temperature proton exchange membrane fuel cells, the performance of high-temperature proton exchange membrane has a great influence on the efficiency, service life and cost of fuel cells.

[0003] Polyvinylpyrrolidone (PVP) is a basic polymer containing nitrogen heterocycles. The amide group in its unit structure makes PVP highly soluble in organic solvents. The basic N and O atoms in the PVP unit can serve as adsorption centers for phosphoric acid (PA), anchoring PA in the polymer network structure to achieve proton conduction. However, PVP has poor mechanical strength and cannot form a membrane alone. Therefore, it needs to be compounded with a skeleton material with good mechanical properties such as polyethersulfone (PES) to improve the mechanical strength of the membrane.

[0004] However, it is still difficult to balance the proton conductivity and mechanical strength of PA-doped polyvinylpyrrolidone-polyethersulfone (PVP-PES) composite membranes. In recent years, researchers have improved the proton conductivity and mechanical strength of composite membranes through cross-linking and inorganic doping modifications, such as doping with phosphotungstic acid, carbon dots, boron nitride, etc. However, ordinary cross-linking agents will cause the polymer chains in the composite membrane to be too tight, reduce PA adsorption, and hinder proton conduction; the existing inorganic fillers have poor compatibility with polymers, resulting in poor dispersion in the composite membrane, easy aggregation, and destruction of the structure of the composite membrane, thereby reducing the mechanical strength of the composite membrane. These factors limit the performance improvement of modified PVP-PES composite membranes. Summary of the invention

[0005] The purpose of the present invention is to provide a cross-linked polyvinyl pyrrolidone-polyether sulfone proton exchange membrane prepared by using a surface brominated tin dioxide cross-linking agent to improve the mechanical strength and proton conductivity of the proton exchange membrane.

[0006] In order to achieve the above-mentioned purpose, the present invention provides a cross-linked polyvinyl pyrrolidone-polyether sulfone high-temperature proton exchange membrane, characterized in that it comprises a membrane main material and a cross-linking agent, the membrane main material comprises polyvinyl pyrrolidone and polyether sulfone, the cross-linking agent is surface brominated tin dioxide, and the added mass ratio of the cross-linking agent is 1% to 4%, calculated on the basis of the membrane main material.

[0007] Furthermore, the mass ratio of polyvinyl pyrrolidone to polyether sulfone is (5-7):(3-5).

[0008] The present invention also provides a method for preparing the above-mentioned cross-linked polyvinyl pyrrolidone-polyether sulfone high temperature proton exchange membrane, comprising:

[0009] Step S1, dissolving polyvinyl pyrrolidone and polyether sulfone in a first polar aprotic solvent to obtain a homogeneous solution;

[0010] Step S2, dispersing the surface brominated tin dioxide in a second polar aprotic solvent to obtain a crosslinking agent solution;

[0011] Step S3, after the homogeneous solution and the cross-linking agent solution are uniformly mixed, a film is formed by a casting method, and the first polar aprotic solvent and the second polar aprotic solvent are removed by heating and evaporation to form a blended film;

[0012] Step S4, soaking the blended membrane in phosphoric acid to obtain a cross-linked polyvinyl pyrrolidone-polyether sulfone high temperature proton exchange membrane.

[0013] Furthermore, the first polar aprotic solvent and the second polar aprotic solvent are the same or different.

[0014] Furthermore, the first polar aprotic solvent and the second polar aprotic solvent are independently selected from any one or more of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone or dimethyl sulfoxide.

[0015] Furthermore, in the step S3, the homogenous solution and the cross-linking agent solution are uniformly mixed at 60° C. to 90° C.

[0016] Furthermore, in step S3, the heating evaporation temperature is 60° C. to 80° C. and maintained for 5 h to 15 h.

[0017] Furthermore, in the step S4, the concentration of the phosphoric acid is 70wt% to 98wt%, and the soaking time is 15h to 30h.

[0018] The present invention also provides a membrane electrode, comprising the cross-linked polyvinyl pyrrolidone-polyether sulfone high-temperature proton exchange membrane.

[0019] The present invention also provides a fuel cell, comprising the above membrane electrode.

[0020] Compared with the prior art, the present invention has at least the following beneficial effects:

[0021] The present invention introduces surface brominated tin dioxide (Br-SnO2) into a polyvinylpyrrolidone-polyethersulfone (PVP-PES) membrane, so that the Br-SnO2 cross-linked PVP-PES high-temperature proton exchange membrane has both high mechanical strength and high proton conductivity. The bromine groups on Br-SnO2 react with the amide groups of PVP to form a cross-linked network and generate quaternary ammonium groups. On the one hand, this cross-linked network enhances the mechanical strength of the proton exchange membrane, while the precise control of the nucleophilic substitution reaction sites avoids excessive cross-linking. On the other hand, the formed quaternary ammonium groups compensate for the reduced PA adsorption caused by the competition between Br-SnO2 and PA for adsorption sites on the polymer main chain. The quaternary ammonium groups react with dihydrogen phosphate (H2PO4 - ) ions, promoting the ionization of PA molecules to release more H + , improving proton conductivity. At the same time, the hydrogen bond network in the strong interaction ion pairs of quaternary ammonium and dihydrogen phosphate builds a continuous and efficient proton transport channel, H + Hopping conduction through this hydrogen bond network promotes the proton transition mechanism and accelerates the proton conduction rate, thereby improving the proton conductivity of the proton exchange membrane without relying on an excessively high proportion of PA adsorption.

[0022] In addition, Br-SnO2, as an inorganic metal oxide material, shows a strong affinity for hydroxyl radicals (- · OH) and hydroxyl peroxide radicals (HOO· -), thereby improving the anti-oxidation stability of the composite membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The graph shows the phosphoric acid absorption and anti-swelling performance of the cross-linked polyvinyl pyrrolidone-polyether sulfone high temperature proton exchange membranes prepared in Examples 1 to 4 of the present invention and the polyvinyl pyrrolidone-polyether sulfone membranes prepared in the comparative example after being immersed in 85 wt % phosphoric acid at room temperature for 24 hours.

[0024] Figure 2 The proton conductivity performance diagram of the cross-linked polyvinyl pyrrolidone-polyether sulfone high temperature proton exchange membrane prepared in Examples 1 to 4 of the present invention and the polyvinyl pyrrolidone-polyether sulfone membrane prepared in the comparative example under non-humidification conditions in the range of 80° C. to 180° C.

[0025] Figure 3 The fuel cell performance diagram of the cross-linked polyvinyl pyrrolidone-polyether sulfone high temperature proton exchange membrane material prepared in Examples 1 to 4 of the present invention and the polyvinyl pyrrolidone-polyether sulfone membrane prepared in the comparative example at 160°C under non-humidified hydrogen and oxygen conditions.

[0026] Among them, PVP / PES represents a comparative example, PP-1%-Br-SnO2 represents Example 1, PP-2%-Br-SnO2 represents Example 2, PP-3%-Br-SnO2 represents Example 3, and PP-4%-Br-SnO2 represents Example 4. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] As described in the background technology, it is difficult for existing polyvinyl pyrrolidone-polyether sulfone (PVP-PES) composite membranes to achieve both high proton conductivity and high mechanical strength. The main reasons are as follows:

[0029] High proton conductivity means that the composite membrane needs to have a high level of phosphoric acid (PA) adsorption capacity to provide sufficient transmission channels for protons and ensure the stability of electrochemical reactions. However, although high levels of PA adsorption can improve proton conductivity, too much PA will be adsorbed around the polymer main chain, increasing the distance between polymer chains, resulting in a decrease in the interaction force between the main chains, which will lead to plasticization of the polymer main chain, causing the proton exchange membrane to swell, and ultimately reducing the mechanical strength of the proton exchange membrane.

[0030] Therefore, it is urgent to develop a PVP-PES composite membrane with both good proton conductivity and high mechanical strength to improve the durability of high-temperature proton exchange membrane fuel cells.

[0031] To solve the above problems, the inventor unexpectedly discovered that by introducing a surface brominated tin dioxide (Br-SnO2) crosslinking agent into the PVP-PES composite membrane, Br-SnO2 and PVP are crosslinked, which effectively improves the proton conductivity of the composite membrane without relying on excessively high proportions of PA adsorption, while ensuring the mechanical strength of the composite membrane. The specific embodiments of the present invention are described in detail below.

[0032] The present invention provides a Br-SnO2 cross-linked polyvinyl pyrrolidone-polyether sulfone (PVP-PES-Br-SnO2, hereinafter referred to as "PP-Br-SnO2") high temperature proton exchange membrane, comprising a membrane main material and a cross-linking agent, wherein the membrane main material comprises polyvinyl pyrrolidone (PVP) and polyether sulfone (PES), and the cross-linking agent is surface brominated tin dioxide (Br-SnO2), and the molecular structures of the PVP, PES, and Br-SnO2 are respectively as follows:

[0033]

[0034] Among them, the mass ratio of PVP and PES is (5-7):(3-5), the added mass ratio of Br-SnO2 is 1%-4%, calculated on the basis of the main material of the membrane; the PVP and PES are commercially available. In this example, the value range of n is 500-1000, and the value range of m is 500-1000.

[0035] In this example, the synthesis method of the Br-SnO2 is as follows: First, 1.5g SnO2 (Shanghai Aladdin Reagent Co., Ltd.) is dispersed in 50mL deionized water to obtain a SnO2 dispersion. Then, 0.6734g (3-bromopropyl) phosphonic acid (Shanghai Bid Pharmaceutical Technology Co., Ltd.) is dissolved in another 50mL deionized water to obtain a (3-bromopropyl) phosphonic acid solution. Within 20min to 30min, the (3-bromopropyl) phosphonic acid solution is slowly added dropwise to the SnO2 dispersion to obtain a mixture. After stirring the mixture at room temperature for 32h to 35h, centrifuge and repeatedly wash the product with deionized water. After washing, dry in an oven at 80°C for 48h. Obtain the Br-SnO2.

[0036] In the PP-Br-SnO2 high temperature proton exchange membrane of the present invention, the Br-SnO2 undergoes a nucleophilic substitution reaction with PVP to form the following cross-linked structure:

[0037]

[0038] The PP-Br-SnO2 high temperature proton exchange membrane provided by the present invention achieves an optimal balance between the mechanical strength and proton conductivity of the composite membrane. The inventors have found through research that the reasons are as follows:

[0039] First, Br-SnO2, as an inorganic crosslinking agent, competes with PA for adsorption sites on the polymer main chain. Therefore, the addition of Br-SnO2 reduces the number of free PAs in the polymer chain, so that the composite membrane will not adsorb too much PA, thereby improving the mechanical strength of the composite membrane. When PA is doped (adsorbed) into the proton exchange membrane, excessive doping of PA will lead to an increase in the free volume between the polymer chains. This phenomenon leads to an increase in the gap between the polymer chains and a decrease in the binding force between the chains, thereby causing the volume expansion (plasticization phenomenon) of the composite membrane. Therefore, the addition of Br-SnO2 can avoid excessive PA doping levels, thereby reducing the swelling rate of the proton exchange membrane after adsorbing PA, and avoiding the reduction in the mechanical strength of the proton exchange membrane caused by excessive PA doping. Moreover, since Br-SnO2 is an inorganic rigid structure, an organic-inorganic structure can be formed in the composite membrane, thereby further improving the mechanical strength of the composite membrane.

[0040] Second, the bromine group on Br-SnO2 reacts with the amide group of PVP through nucleophilic substitution reaction to form a cross-linked network and generate quaternary ammonium groups. On the one hand, the cross-linked network can enhance the mechanical strength of the composite membrane, while the nucleophilic substitution reaction at specific sites helps to precisely control the cross-linking points in the composite membrane and avoid excessive cross-linking that may be caused by traditional cross-linking agents. On the other hand, the quaternary ammonium group can compensate for the decrease in proton conductivity caused by the reduction in PA adsorption. The quaternary ammonium group has a positive charge and can attract the dihydrogen phosphate (H2PO4 - ) ions to form a strong interaction ion pair of quaternary ammonium and dihydrogen phosphate, which enhances the retention capacity of the adsorbed PA and maintains the proton conductivity of the composite membrane, thereby improving its durability; moreover, this interaction can promote the ionization reaction of PA molecules, thereby releasing more H + , thereby improving the proton conductivity of the composite membrane. At the same time, during the proton conduction process, H + The hydrogen bond network between the quaternary ammonium-dihydrogen phosphate ion pairs can be used for hopping conduction, promoting the proton transition mechanism, thereby accelerating the proton conduction speed. Therefore, the present invention can improve the proton conductivity of the composite membrane without relying on too high a proportion of PA adsorption.

[0041] In addition, Br-SnO2 is an inorganic metal oxide material, which shows the ability to scavenge hydroxyl radicals (-OH) and peroxyhydroxyl radicals (HOO-) through redox cycles, thereby also improving the antioxidant stability of PP-Br-SnO2 high-temperature proton exchange membrane.

[0042] The preparation method of the PP-Br-SnO2 high temperature proton exchange membrane of the present invention comprises:

[0043] Step S1, dissolving PVP and PES in a first polar aprotic solvent to obtain a homogeneous solution.

[0044] The first polar aprotic solvent includes, but is not limited to, any one or more of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone or dimethyl sulfoxide.

[0045] Step S2, dispersing Br-SnO2 in a second polar aprotic solvent to obtain a crosslinking agent solution.

[0046] The second polar aprotic solvent and the first polar aprotic solvent may be the same or different. The second polar aprotic solvent includes, but is not limited to, any one or more of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone or dimethyl sulfoxide.

[0047] Step S3, after the homogeneous solution and the cross-linking agent solution are uniformly mixed, a film is formed by a casting method, and the first polar aprotic solvent and the second polar aprotic solvent are removed by heating and evaporation to form a blended film.

[0048] The homogeneous solution and the crosslinking agent solution are mixed uniformly at 60° C. to 90° C. At this temperature, Br-SnO2 and PVP undergo a crosslinking reaction to form a crosslinked structure, and this temperature is conducive to better dispersion of Br-SnO2 in the homogeneous solution to form a uniform solution.

[0049] The heating evaporation temperature is 60° C. to 80° C. and maintained for 5 h to 15 h, so as to completely remove the first polar aprotic solvent and the second polar aprotic solvent to facilitate film formation.

[0050] Step S4, soaking the blended membrane in phosphoric acid to obtain a cross-linked polyvinyl pyrrolidone-polyether sulfone membrane high-temperature proton exchange membrane.

[0051] The concentration of the phosphoric acid is 70wt% to 98wt% and the soaking time is 15h to 30h, so that the blended membrane fully absorbs the phosphoric acid to form a phosphoric acid-doped cross-linked polyvinyl pyrrolidone-polyether sulfone membrane high-temperature proton exchange membrane.

[0052] Unless otherwise specified, the chemicals used in the present invention are all conventional commercially available chemical reagents. These chemicals can be purchased from a number of chemical reagent suppliers and do not require special preparation or synthesis.

[0053] The present invention is further described in detail below in conjunction with specific embodiments.

[0054] Example 1

[0055] This embodiment provides a surface brominated tin dioxide cross-linked polyvinyl pyrrolidone-polyether sulfone (PP-Br-SnO2) high temperature proton exchange membrane.

[0056] The preparation method of the PP-Br-SnO2 high temperature proton exchange membrane is as follows:

[0057] Step S101, using polyvinyl pyrrolidone (PVP) and polyether sulfone (PES) as raw materials, using N-methyl pyrrolidone solution as solvent, adding the PVP and PES into the N-methyl pyrrolidone solution, the mass ratio of PVP to PES is 7:3, stirring at room temperature for 12 hours to dissolve it, and obtaining a polyvinyl pyrrolidone-polyether sulfone (PVP-PES) solution.

[0058] Step S102, adding Br-SnO2 to the N-methylpyrrolidone solution, stirring at room temperature and performing ultrasonic dispersion to obtain a Br-SnO2 uniformly dispersed suspension. The mass ratio of the Br-SnO2 to the total mass of the PVP and PES is controlled to be 1:100, that is, 1wt% of Br-SnO2 is added.

[0059] Step S103, adding the Br-SnO2 uniformly dispersed suspension into the PVP-PES solution, stirring and ultrasonically dispersing at 80° C. to obtain a membrane solution in which the total mass fraction of PVP, PES and Br-SnO2 in the solution is 15wt%.

[0060] Step S104, forming a film by a casting method, casting the membrane solution in step S103 on a glass plate, heating at 60°C for 12 hours, and volatilizing and removing N-methylpyrrolidone to obtain a Br-SnO2 cross-linked polyvinylpyrrolidone-polyethersulfone (PP-Br-SnO2) blended membrane.

[0061] Step S105, soaking the PP-Br-SnO2 blended membrane in 85wt% PA at room temperature for 24 hours and then taking it out to obtain the desired composite high-temperature proton exchange membrane, which is recorded as PP-1%-Br-SnO2.

[0062] Example 2

[0063] The difference between this embodiment and embodiment 1 is that in step S102, the added mass ratio of Br-SnO2 is 2 wt %. The obtained composite high temperature proton exchange membrane is recorded as PP-2%-Br-SnO2.

[0064] Example 3

[0065] The difference between this embodiment and embodiment 1 is that in step S102, the added mass ratio of Br-SnO2 is 3 wt %. The obtained composite high temperature proton exchange membrane is recorded as PP-3%-Br-SnO2.

[0066] Example 4

[0067] The difference between this embodiment and embodiment 1 is that in step S102, the added mass ratio of Br-SnO2 is 4 wt %. The obtained composite high temperature proton exchange membrane is recorded as PP-4%-Br-SnO2.

[0068] Comparative Example

[0069] This comparative example provides a polyvinyl pyrrolidone-polyether sulfone (PVP-PES) high temperature proton exchange membrane, which is different from Example 1 in that Br-SnO2 is not added. The specific preparation process of the PVP-PES high temperature proton exchange membrane is as follows:

[0070] PVP and PES were added to N-methylpyrrolidone solution (mass ratio: PVP:PES = 7:3) and stirred at room temperature for 12 hours to make them dissolve evenly. The total mass fraction of PVP, PES, and Br-SnO2 in the solution was 15wt% of a uniform transparent solution; the film was formed by casting, the uniform transparent solution was cast on a glass plate, heated at 60°C for 12 hours, and N-methylpyrrolidone was volatilized to obtain a polyvinylpyrrolidone-polyethersulfone (PVP-PES) blended membrane. The PVP-PES blended membrane was soaked in 85wt% phosphoric acid at room temperature for 24 hours and then taken out to obtain the desired high-temperature proton exchange membrane, which was recorded as PVP / PES.

[0071] The high temperature proton exchange membranes with different doping amounts obtained in Examples 1 to 4 and the comparative example were subjected to the following off-line and on-line tests.

[0072] With reference to GB / T 20042.3-2022, the obtained high-temperature proton exchange membrane was tested for swelling rate. The specific operating conditions were as follows: under constant temperature and humidity conditions of 23°C ± 2°C and 50% ± 5%, the initial length L0 and initial width W0 of the sample were measured with a caliper, the thickness d0 of the sample was measured with a thickness gauge, and the initial volume V0 = L0 × W0 × d0 was calculated. After the sample was soaked for 24 hours at room temperature and a phosphoric acid concentration of 85%, the length L and width W of the sample were measured with a caliper, the thickness d of the sample was measured with a thickness gauge, and the volume after soaking V = L × W × d was calculated. The swelling rate E v =V0 / V.

[0073] Referring to GB / T 20042.3-2022, the proton conductivity of the obtained high temperature proton exchange membrane was tested. The specific operating conditions were: at a temperature of 80°C to 180°C and a humidity of 0%, a conductivity test device was connected to an electrochemical impedance tester.

[0074] With reference to GB / T 20042.5-2009, the obtained high temperature proton exchange membrane was made into a high temperature proton exchange membrane fuel cell, and a polarization curve test was carried out. The specific operating conditions were: the operating temperature of the single cell was 160°C, the anode was fed with pure hydrogen, the cathode was fed with normal pressure oxygen, and the ratio of cathode feed to anode feed was 1:1.

[0075] The test results are as follows Figures 1 to 3 shown.

[0076] See also Figure 1 , the phosphoric acid adsorption (doping) rate and swelling rate of the proton exchange membranes prepared in Examples 1 to 4 of the present invention and the comparative example were measured. It can be seen from the figure that after phosphoric acid adsorption, the phosphoric acid adsorption rates of the membranes prepared in Examples 1 to 4 of the present invention and the comparative example were measured to be 352.78%, 342.16%, 342.16%, 323.86%, and 416.84%, respectively. The corresponding swelling rates were 209.54%, 189.72%, 172.41%, 165.97%, and 231.3%, respectively. Compared with the comparative example, the PA adsorption rate of the PP-Br-SnO2 proton exchange membrane prepared in Examples 1 to 4 of the present invention maintained a high level, and the swelling rate was low; while the PA adsorption rate of the comparative example was too high, resulting in a high swelling rate, which was not conducive to the mechanical properties of the proton exchange membrane. The PA adsorption rates of Examples 1 to 4 are slightly reduced compared to the control example, which proves that Br-SnO2 will compete with PA for the adsorption sites on the polymer main chain. Therefore, the addition of Br-SnO2 can effectively avoid the reduction of the interchain binding force caused by excessive doping of PA, thereby reducing the deformation and swelling of the proton exchange membrane, and further proving that the PP-Br-SnO2 high-temperature proton exchange membrane prepared by the present invention has good mechanical strength.

[0077] See also Figure 2 , the proton conductivity of the proton exchange membranes prepared in Examples 1 to 4 of the present invention and the comparative example was measured. As can be seen from the figure, at 100°C, the proton conductivities of Examples 1 to 4 of the present invention and the comparative example were 0.0729 S·cm -1 、0.0823S·cm -1 、0.0879S·cm -1 、0.0795S·cm -1 、0.0704S·cm -1 At 160°C, the proton conductivity of Examples 1 to 4 of the present invention and the comparative example were measured to be 0.1097 S·cm-1 、0.1237S·cm -1 、0.1296S·cm -1 、0.1179S·cm -1 , 0.0981S·cm -1 Compared with the comparative example, the PP-Br-SnO2 proton exchange membranes prepared in Examples 1 to 4 of the present invention have higher proton conductivity and better proton conductivity, which proves that the quaternary ammonium groups generated by cross-linking Br-SnO2 and PVP in the present invention can effectively compensate for the decrease in proton conductivity (proton conductivity) caused by the decrease in PA adsorption, and the attraction of the quaternary ammonium groups to negative charges is conducive to the formation of quaternary ammonium groups and dihydrogen phosphate (H2PO4 - ) forms a strong quaternary ammonium-dihydrogen phosphate ion pair, which promotes the ionization of PA and forms more H + , and enhance the retention capacity of adsorbed PA, thereby improving the proton conductivity of the proton exchange membrane. In addition, the strong hydrogen bond network between ion pairs makes H + Able to conduct transitions and accelerate H + conduction, further improving the proton conductivity of the proton exchange membrane.

[0078] See also Figure 3 The fuel cell performance diagram of the proton exchange membranes prepared in Examples 1 to 4 of the present invention and the comparative example was measured. It can be seen from the figure that at 0.1 A / cm 2 When the membrane electrode voltages of the proton exchange membranes prepared by the embodiments 1 to 4 of the present invention and the comparative example were measured to be 0.748 V, 0.769 V, 0.754 V, 0.757 V, and 0.708 V, respectively. The power densities of the fuel cells prepared by the proton exchange membranes prepared by the embodiments 1 to 4 of the present invention and the comparative example were measured to be 74.8 mW·cm -2 、76.9mW·cm -2 、75.4mW·cm -2 、75.7mW·cm -2 、70.8mW·cm -2 . At 0.5A / cm 2 When the membrane electrode voltages of the proton exchange membranes prepared by the embodiments 1 to 4 of the present invention and the comparative example are measured to be 0.560 V, 0.613 V, 0.618 V, 0.576 V, and 0.501 V, respectively. The power densities of the fuel cells prepared by the proton exchange membranes prepared by the embodiments 1 to 4 of the present invention and the comparative example are measured to be 280.0 mW·cm -2 、306.5mW·cm -2 、309.0mW·cm -2 、288mW·cm -2 、250.5mW·cm -2At 1.0A / cm 2 When the membrane electrode voltages of the proton exchange membranes prepared by the embodiments 1 to 4 of the present invention and the comparative example were measured to be 0.343 V, 0.428 V, 0.463 V, 0.381 V, and 0.276 V, respectively. The power densities of the fuel cells prepared by the proton exchange membranes prepared by the embodiments 1 to 4 of the present invention and the comparative example were measured to be 343.0 mW·cm -2 、428.0mW·cm -2 、463.0mW·cm -2 、381.0mW·cm -2 、276.0mW·cm -2 Compared with the comparative example, the membrane electrode voltage of the PP-Br-SnO2 proton exchange membrane prepared in Examples 1 to 4 of the present invention is higher, which means that the membrane electrode polarization loss is smaller and the power density of the fuel cell is higher, which proves that the PP-Br-SnO2 high temperature proton exchange membrane prepared by the present invention has high proton conductivity during operation, and the fuel cell prepared by using the PP-Br-SnO2 high temperature proton exchange membrane has small polarization loss during operation, which is beneficial to improve the durability of the fuel cell.

[0079] In summary, the present invention achieves a balance between high mechanical strength and high proton conductivity of high-temperature proton exchange membranes by introducing surface brominated tin dioxide (Br-SnO2) into polyvinylpyrrolidone-polyethersulfone (PVP-PES) membranes. The bromine groups on Br-SnO2 react with the amide groups of PVP to form a cross-linked network and generate quaternary ammonium groups, which enhances the mechanical strength of the membrane while precisely controlling the cross-linking points to avoid excessive cross-linking. The quaternary ammonium groups not only compensate for the reduced adsorption of PA caused by the competition between Br-SnO2 and dihydrogen phosphate (H2PO4 - ) ions form strong interaction ion pairs, promoting the ionization of PA molecules and releasing more H + , improving proton conductivity. The hydrogen bond network constructed by these ion pairs is H + It provides a continuous and efficient transmission channel, promotes the proton transition mechanism, and accelerates the proton conduction rate, thereby improving the proton conductivity of the proton exchange membrane without relying on a high proportion of PA adsorption.

[0080] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A cross-linked polyvinyl pyrrolidone-polyether sulfone high temperature proton exchange membrane, characterized in that: The invention comprises a main membrane material and a cross-linking agent, wherein the main membrane material comprises polyvinyl pyrrolidone and polyether sulfone, the cross-linking agent is surface brominated tin dioxide, and the added mass ratio of the cross-linking agent is 1% to 4% based on the main membrane material.

2. The cross-linked polyvinyl pyrrolidone-polyether sulfone high temperature proton exchange membrane according to claim 1, characterized in that: The mass ratio of polyvinyl pyrrolidone to polyether sulfone is (5-7):(3-5).

3. A method for preparing a cross-linked polyvinyl pyrrolidone-polyether sulfone high temperature proton exchange membrane as claimed in claim 1 or 2, characterized in that: Include: Step S1, dissolving polyvinyl pyrrolidone and polyether sulfone in a first polar aprotic solvent to obtain a homogeneous solution; Step S2, dispersing the surface brominated tin dioxide in a second polar aprotic solvent to obtain a crosslinking agent solution; Step S3, after the homogeneous solution and the cross-linking agent solution are uniformly mixed, a film is formed by a casting method, and the first polar aprotic solvent and the second polar aprotic solvent are removed by heating and evaporation to form a blended film; Step S4, soaking the blended membrane in phosphoric acid to obtain a cross-linked polyvinyl pyrrolidone-polyether sulfone high temperature proton exchange membrane.

4. The preparation method according to claim 3, characterized in that: The first polar aprotic solvent and the second polar aprotic solvent are the same or different.

5. The preparation method according to claim 4, characterized in that: The first polar aprotic solvent and the second polar aprotic solvent are independently selected from any one or more of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone or dimethyl sulfoxide.

6. The preparation method according to claim 3, characterized in that: In the step S3, the homogenous solution and the cross-linking agent solution are mixed uniformly at 60° C. to 90° C.

7. The preparation method according to claim 3, characterized in that: In the step S3, the heating evaporation temperature is 60° C. to 80° C. and maintained for 5 h to 15 h.

8. The preparation method according to claim 3, characterized in that: In the step S4, the concentration of the phosphoric acid is 70 wt% to 98 wt%, and the soaking time is 15 h to 30 h.

9. A membrane electrode, characterized in that: It comprises the cross-linked polyvinyl pyrrolidone-polyether sulfone high temperature proton exchange membrane as claimed in claim 1 or 2.

10. A fuel cell, characterized in that: A membrane electrode comprising the membrane electrode according to claim 9.

Citation Information

Patent Citations

  • Proton exchange membrane and preparation method thereof

    CN103904344A

  • Laminate useful as a membrane-electrode assembly for fuel cells, production process therefor and a fuel cell provided with the laminate

    US20050042489A1

  • Hydrophilic polymer-oxide-phosphoric acid compositions for proton conducting membranes

    US20060148953A1